种1H-1,2,4-三氮唑的合成工艺 (2018)
本发明公开了种1H-1,2,4-三氮唑的合成工艺，其合成步骤如下：(1)向高压反应釜中依次加入甲酸酯、水合肼和铵盐，在密封搅拌状态下，将反应釜加压并缓慢升温至反应温度，反应结束后，缓慢降低反应温度并利用余热蒸出副产物甲醇，得到白色乳状物。(2)将所述白色乳状物转移至反应釜中，加入乙醇，加热回流反应得到混合液，将混合液经滤筒热过滤至结晶釜，滤液在结晶釜中冷却至室温，析出白色晶体，离心分离后，经热风烘箱干燥即可得到1H-1,2,4-三氮唑。本发明通过甲酸酯和铵盐在高温高压条件下分解的氨直接氨解得到甲酰胺与水合肼反应，有效的提高了整个化学反应速度，降低了反应温度，提高了产品收率，整体合成工艺简单，能耗低，三废排放少。 The invention discloses a synthesizing process of 1H-1,2,4-triazole, comprising the following synthesizing steps: (1) adding formic ether, hydrazine hydrate and ammonium salt in sequence into a high-pressure reaction kettle, pressurizing the reaction kettle and gradually heating up to a reaction temperature under a sealed stirring state, gradually lowering down the reaction temperature after the reaction is complete and using the after heat to evaporate the byproduct methyl alcohol, thereby obtaining a white emulsion matter; (2) transferring the white emulsion matter into the reaction kettle, adding ethyl alcohol, heating and refluxing to obtain a mixture solution, hot filtering the mixture solution by a